5c-2+c=-8-4c-7
5c-2+c-c=-8-4c-1-c
5c-2=-9-5c
5c-2-5c=-9-5c-5c
-2=-9-10c
-2+9=-9-10c+9
7=10c
c=7/10
c=0.7
THE ANSWER IS 0.7
2006-11-24 05:36:52
·
answer #1
·
answered by chocolate.smartie 2
·
0⤊
1⤋
5c - 2 + c = - 8 - 4c - 1
6c - 2 = - 9 - 4x
6c - 2 + 4c = - 9 - 4c + 4c
10c - 2 = - 9
10c - 2 + 2 = - 9 + 2
10c = - 7
10c/10 = - 7/10
c = - 7/10
c = 0.7
The answer is c = - 0.7
- - - - - - -s-
2006-11-24 15:05:59
·
answer #2
·
answered by SAMUEL D 7
·
0⤊
0⤋
5c - 2 + c = -8 - 4c - 1
6c - 2 = -9 - 4c
10c -2 = -9
10c = -7
c = -7 / 10
c = -0.7
2006-11-24 14:56:13
·
answer #3
·
answered by Jen 2
·
0⤊
0⤋
5c-2+c=-8-4c-1
add like terms 6c-2=-4c-9
add -4c to get rid of +4c on both sides (properties of equality)
10c-2=-9
add 2 to get rid of -2 on both sides (properties of equality)
10c=-7
divide both sides by 2 (properties of equality)
c=0.7
2006-11-24 15:45:50
·
answer #4
·
answered by Lauren N 2
·
0⤊
0⤋
c = -7/10
2006-11-24 13:42:32
·
answer #5
·
answered by Fahd Shariff 3
·
0⤊
0⤋
5c - 2 + c = -8 - 4c - 1
6c -2 = -4c - 9
10c = -7
c = -0.7
2006-11-24 13:33:33
·
answer #6
·
answered by blapath 6
·
0⤊
1⤋
c = -7/10
2006-11-24 13:38:41
·
answer #7
·
answered by ag_iitkgp 7
·
0⤊
1⤋
6c -2 = -4c - 9
7= -10c
c= - 7/10
2006-11-24 13:33:15
·
answer #8
·
answered by Anonymous
·
0⤊
1⤋
6c + 2 =-9 -4c
11 = -8c
-11/8 = c
2006-11-24 13:32:15
·
answer #9
·
answered by Sylvie M 3
·
0⤊
1⤋
10c=-7
c= -7/10
2006-11-24 13:38:54
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋